Large-Scale Oceanic Variability Associated with the Madden-Julian Oscillation during the CINDY/DYNAMO Field Campaign from Satellite Observations - Chunzai Wang; Weiqing Han; Sue Chen; Maria Flatau; Tommy G. Jensen; Toshiaki Shinoda (Remote Sensing, 2013)
During the CINDY/DYNAMO field campaign (fall/winter 2011), intensive measurements of the upper ocean, including an array of several surface moorings and ship observations for the area around 75°E–80°E, Equator-10°S, were conducted. In this study, large-scale upper ocean variations surrounding the intensive array during the field campaign are described based on the analysis of satellite-derived data. Surface currents, sea surface height (SSH), sea surface salinity (SSS), surface winds and sea surface temperature (SST) during the CINDY/DYNAMO field campaign derived from satellite observations are analyzed. During the intensive observation period, three active episodes of large-scale convection associated with the Madden-Julian Oscillation (MJO) propagated eastward across the tropical Indian Ocean. Surface westerly winds near the equator were particularly strong during the events in late November and late December, exceeding 10 m/s. These westerlies generated strong eastward jets (>1 m/s) on the equator. Significant remote ocean responses to the equatorial westerlies were observed in both Northern and Southern Hemispheres in the central and eastern Indian Oceans. The anomalous SSH associated with strong eastward jets propagated eastward as an equatorial Kelvin wave and generated intense downwelling near the eastern boundary. The anomalous positive SSH then partly propagated westward around 4°S as a reflected equatorial Rossby wave, and it significantly influenced the upper ocean structure in the Seychelles-Chagos thermocline ridge about two months after the last MJO event during the field campaign. For the first time, it is demonstrated that subseasonal SSS variations in the central Indian Ocean can be monitored by Aquarius measurements based on the comparison with in situ observations at three locations. Subseasonal SSS variability in the central Indian Ocean observed by RAMA buoys is explained by large-scale water exchanges between the Arabian Sea and Bay of Bengal through the zonal current variation near the equator.